Geospatial metadata extraction from product description document applying methods from ontology engineering. (1st October 2010) - Abugessaisa, Imad
Metadata creation is a bottleneck in European Union (EU) INSPIRE Directive. Firstly the paper presents results from a conformance test conducted at Swedish Land Survey. The results of the testing show a gap between the current statuses of metadata and INSPIRE demands. Secondly the paper introduces an ontology-engineering approach to support extraction of metadata from annotated text documents. This approach can be used for generating metadata in Ontology Web Language (OWL) format that can be reused in a Geography Markup Language (GML) documents instance. Catalogue service of the Swedish geoportal to INSPIRE can employ this approach to generate dataset-level metadata.